Appraisal of the employment tax rebate in Kenya: study of firms registered under Kenya Association of Manufacturers - Muthoni, L. J. (Strathmore University, 2025)
Kenya’s substantial and youthful demographic, representing approximately 62% of the working-age population, offers a promising avenue for economic advancement. However, the realization of this potential is impeded by high youth unemployment rates which is exacerbated by among others, lack of work relevant skills and experience. To encourage employers to hire and train fresh graduates, the Kenyan government implemented a tax incentive in 2016, which provided employers with a 50% tax rebate on the salaries paid to fresh graduates. The objective of the study is to appraise the tax rebate scheme to examine the gaps in its policy design and sector specific challenges faced by firms registered under the Kenya Association of Manufacturers. Anchored on the Incentive Theory, the study adopted a qualitative approach and gathered insights from the selected firms on their experience and perceptions of the rebate. Data was collected using open ended interview questions from the target population of 1,212 firms under the Kenya Association of Manufacturers. Stratified and purposive sampling were used to select 44 firms. Data collected from interviews was transcribed and organized into thematic areas to identify recurring patterns, themes, and topics. Findings collected from the 42 firms who responded reveal that awareness of the rebate is generally low. Firms who were aware of the rebate faced barriers in accessing it such as lack high eligibility requirements, limited timeframe, inadequate information on the rebate and complex application process. The study highlights that while rebate holds promise of addressing youth unemployment, flaws in its design and aspects of implementation have hindered its uptake. The study recommends a reduction of the minimum hiring threshold, expansion of the time frame, increased awareness campaigns through multiple channels, simplification and digitalization of the application process, and targeted support to SME’s and sectors facing distinct challenges. These measures will ensure the tax rebate is well aligned to the interests of employers and improve its uptake as per the principles of the Incentives Theory. Key words: Employment Tax Rebate, Financial incentives, Fresh graduates, Kenya association of Manufacturers
Full - text thesis